DIAGNOSIS DEPRESI SEBAGAI PERSEPSI DARI ALAM BAWAH SADAR TOKOH UTAMA PADA CERPEN DURIAN KARYA DJENAR MAESA AYU - Yuli Aisyah putri Anam (Mahakarya: Jurnal Mahasiswa Ilmu Budaya, 2022)
This study aimed at analyzing a short story by Djenar Maesa Ayu in her book entitled Mereka Bilang, Saya Monyet. The short story discussed in this research was called Durian. The objective of this study was to reveal the triggers of mental disorders experienced by the main character in the short story Durian. The object of this research was Durian, with the psychology of Hyza as the formal object of this research. The short story Durian became a primary data source, and all articles related to Durian acted as secondary data sources. The data collection technique utilized in the recent study was analytical, including reading, listening, and taking notes. The research results revealed that the mental disorders experienced by Hyza's character came from past experiences that could not be resolved, so it accompanied the character's abnormal mental development. Those experiences triggered the character's subconscious desires that affect the character's conscious mind. Hallucinations and fears are a form of mental disorder as a result of the perception from the past experiences.